The Association Between Serum Hyaluronic Acid Levels and Routine Liver Function Tests in Liver Fibrotic HCV Patients - Abdelmonem, M; Wasim, H; Elhusseny, A; Eldaly, R; Saleh Abdelfattah, M; Abdelmageed, M (American journal of clinical pathology, 2022)
Abstract Introduction/Objective Liver fibrosis is the excessive accumulation of extracellular matrix proteins, including collagen, that occurs in most types of chronic liver diseases. Advanced liver fibrosis results in cirrhosis, liver failure, and portal hypertension and often requires liver transplantation. Markers (NIM) of Liver Fibrosis, such as hyaluronic acid, help evaluate the stage of fibrosis in patients with liver fibrosis. This study aims to investigate whether or not there is a correlation between serum hyaluronic acid levels and liver function tests in patients who suffer from chronic HCV-induced liver fibrosis. Methods/Case Report This study was conducted on 118 (60 males and 58 females) patients recruited from Internal Medicine Dept., Mansoura University Hospitals, Egypt. The patients were diagnosed with chronic HCV-induced liver fibrosis. Also, we included 50 healthy comparable control subjects (27 males and 23 females). Routine laboratory tests such as AST, ALT, albumin, total bilirubin, and platelets count were performed. The APRI was calculated as [AST/ (upper limits of normal)/ platelets count 109/L]×100. The AST-ALT ratio was calculated as [AST/ ALT]. According to the manufacturer's instructions, the serum levels of hyaluronic acid were measured by radioimmunoassay. Results (if a Case Study enter NA) We observed a statistically significant positive correlation was found between serum hyaluronic acid levels and APRI (r=0.3, p=0.001), ALT (r=0.3, p=0.003), AST (r=0.3 and p=0.01), and total bilirubin (r=0.3 and p=0.002). Furthermore, there was a statistically significant negative correlation between serum hyaluronic acid levels and albumin (r= -0.43, p=0.0001), and platelets count (r= -0.4, p=0.0001). Conclusion The levels of hyaluronic acid in the body and the results of other liver function tests tend to rise in tandem, which suggests a significant relationship between the two. This may assist us in constructing an accurate picture of the patient's condition, which will lead to a more precise diagnosis.